Enalapril improves endothelial function in patients with migraine: A randomized, double-blind, placebo-controlled trial - Javanmard, Shaghayegh Haghjooy (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: There are increasing evidences of endothelial dysfunction in migraine. The ACE-inhibitors have previously been shown to be effective in migraine prophylaxis. Furthermore, ACE inhibitors have beneficial effects on endothelial dysfunction. We therefore investigated whether Enalapril is effective in endothelial function improvement. METHODS: In this randomized clinical trial, 10 mg Enalapril daily was compared with matched placebo in 40 patients with migraine for two months. Flow Mediated Dilation (FMD), serum total nitrite and C-reactive protein (CRP) were measured in all patients at the baseline and after 2 months. RESULTS: patients’ FMD increased in the case group after treatment with Enalapril (p = 0.002) while there was no significant change in control group. Total nitrite concentration increased in case group (p = 0.000), while there was no significant difference before treatment. There was no significant difference in the CRP concentrations in two groups. CONCLUSIONS: These results indicate that ACE inhibition can improve endothelial function in patients with migraine, as it has been shown by both FMD and serum levels of nitric oxide. The mechanism could be either that Enalapril limits the angiotensin IIinduced production of superoxide radicals which would normally inactivate nitric oxide, or that it may increase bradykinin-mediated nitric oxide release.